2017
DOI: 10.18632/oncotarget.18088
|View full text |Cite
|
Sign up to set email alerts
|

RNase alleviates neurological dysfunction in mice undergoing cardiac arrest and cardiopulmonary resuscitation

Abstract: Cardiac arrest (CA) is one of the leading lethal factors. Despite cardiopulmonary resuscitation (CPR) procedure has been consecutively improved and lots of new strategies have been developed, neurological outcome of the patients experienced CPR is still disappointing. Ribonuclease (RNase) has been demonstrated to have neuroprotective effects in acute stroke and postoperative cognitive impairment, possibly through acting against endogenous RNA that released from damaged tissue. However, the role of RNase in pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…Besides, 20, 15 and 12 of 25 mice survived in the CA/CPR group on day 1, 2 and 3 after CA/CPR procedures, respectively. The survival rates were 80%, 60%, and 48%, respectively, which was similar to previously published literature [ 17 , 18 ]. In our settings, the mice received five minutes of CA, and subsequent CPR performance exhibited a remarkable abnormality in cognitive function ( Figure 1E ).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Besides, 20, 15 and 12 of 25 mice survived in the CA/CPR group on day 1, 2 and 3 after CA/CPR procedures, respectively. The survival rates were 80%, 60%, and 48%, respectively, which was similar to previously published literature [ 17 , 18 ]. In our settings, the mice received five minutes of CA, and subsequent CPR performance exhibited a remarkable abnormality in cognitive function ( Figure 1E ).…”
Section: Resultssupporting
confidence: 90%
“…In this study, we demonstrated that mice surviving after 5 minutes of CA displayed remarkable abnormalities in the contextual fear-conditioning test and neurologic score ( Figure 1 ). The survival rate on day 3 after CA/CPR was 48%, which was quantitatively in good agreement with earlier reports [ 17 , 18 ]. It was indicated that the animal model of CA/CPR in our study was reliable.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although CA can lead to ischemia/reperfusion (I/R) injury in every organ in the body, it is especially detrimental to the brain and the heart. The principal pathological cause of organ damage is excessive apoptosis and autophagy (4,5), the extent of which has been found to correlate with poor neurological prognosis (6)(7)(8). A number of studies have demonstrated that hypothermia can attenuate neurological damage following I/R injury by reducing neural apoptosis and preventing autophagy overactivation (4,9,10).…”
Section: Introductionmentioning
confidence: 99%